Ghrelin is essential for lowering blood pressure during torpor - Matsui, Kazuma; Ida, Takanori; Oishi, Kanae; Kojima, Masayasu; Sato, Takahiro (Frontiers in Endocrinology, 2024)
Introduction: Daily torpor is an active hypothermic phenomenon that is observed in some mammals and birds during fasting. A decrease in blood pressure has also been observed in torpor; however, there remains a lack of knowledge of the underlying mechanism. We have previously reported that ghrelin, an orexigenic hormone, has a hypothermic effect and is essential for the induction and maintenance of torpor. It is also known that the ghrelin secretion is enhanced during fasting and that ghrelin receptors are distributed in the cardiovascular system. Therefore, this study was conducted to test the hypothesis that ghrelin is actively involved in the regulation of blood pressure during torpor induction. Methods: Male wild-type and ghrelin gene-deficient mice were generated by homologous recombination as previously reported (1). Mice, 10 weeks old, were included in this study and housed five per cage. The mice were maintained on a 12-h light/dark cycle (lights on from 7:00 to 19:00) with access to food and water ad libitum. Results: The continuous measurement of blood pressure using a telemetry system showed that induction of torpor by fasting did not decrease blood pressure in ghrelin gene-deficient mice. The analysis of heart rate variability revealed that sympathetic nerve activity was predominant in ghrelin-deficient mice during fasting. Furthermore, these features were cancelled by administration of a ghrelin receptor agonist and were comparable to those in wild-type mice. Discussion: In this study, we showed that blood pressure was elevated in ghrl -/-mice and that the blood pressure rhythm was abnormal. Furthermore, we showed that the ghrelin gene deficiency does not cause sufficient blood pressure reduction upon entry into the torpor, and that the administration of the ghrelin receptor agonist, GHRP-6, causes blood pressure reduction associated with torpor. Thus, we have shown for the first time that the active role of ghrelin is essential for active blood pressure reduction associated with torpor, and that this action is mediated by the inhibition of sympathetic nerve activity by ghrelin.